Semiconductive properties of anodic niobium oxides - Sá,A.I. de (2006)
The semiconductive properties of anodic niobium oxides formed at constant potential and constant current density to different final voltages have been examined by Mott-Schottky analysis. Thin anodic oxides were formed on sputtered niobium specimens at constant potential in the range of 2.5 to 10 V Ag/AgCl in a borate buffer solution. Thicker oxides were formed, also on sputtered niobium specimens, at a constant current density of 5 mA cm-2 in 0.1 M ammonium pentaborate solution to final voltages of 10, 50 and 100 V. Capacitance measurements were performed in a borate buffer solution of pH 8.8, at a frequency range of 200 to 2000 Hz, at a sweep rate of 5 mV s-1 from +2.5 to -1 V Ag/AgCl. The results obtained show n-type semiconductor behaviour with a carrier density in the range of 8 ´ 10(18) - 6 ´ 10(19) cm-3 on films formed to 10 V. Thicker films showed lower carrier densities in the range of 1 ´ 10(18) - 2 ´ 10(18) cm-3 with a calculated charge depletion layer of 33-36 nm.